(untitled) (Revista Innova Educación, 2024)
In the face of a context that demands the formation of individuals with a broad perspective of the world, the Association of Universities Entrusted to the Society of Jesus in Latin America (AUSJAL) promotes intercultural dialogue through various projects. One such project is Collaborative Online International Learning (COIL). This essay presents the systematization of a COIL experience, from its design to its implementation. Students and professors from the Central American University José Simeón Cañas (UCA, El Salvador) and the Jesuit University of Guadalajara (ITESO, Mexico) achieved learning objectives related to values such as solidarity, social justice, intercultural dialogue, and the formation of individuals committed to building a more inclusive world. The COIL methodology involved: flexible duration, groups of students sharing tasks and projects, an initial activity, synchronous or asynchronous interaction, and group reflection on the shared experience. The systematization of this experience has a qualitative approach, assuming social phenomena from the perspective of the participating actors. The results showed that the exchange between students from different countries allowed them to collaboratively construct, in a virtual environment, an academic text that argued their position on social issues, aligned with the UN Sustainable Development Goals (SDGs), from an intercultural perspective. The participants achieved common goals, built collaborative learning networks, and expressed improvement in their skills for respectful and empathetic communication that enriched them interculturally, allowing them to identify points of convergence regarding other contexts, from a regional perspective.